Morphoanatomical atlas of grass leaves, culms, and caryopses - Gandhi, Dhara; Albert, Susy (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"This new volume, Morphoanatomical Atlas of Grass Leaves, Culms, and Caryopses, features the studied anatomical details of different parts of 100 wild grass species and provides a comprehensive overview of existing knowledge. Each of the three sections of the volume (leaf grass, culm, and caryopses) discusses and illustrates the diagnostic histological features, along with statistical analyses on the quantitative and qualitative data. The descriptions of these grasses, particularly those growing in the grasslands of the Panchmahal and Dahod districts of India, are supplemented with microphotographs and keys for the taxa concentrate upon diagnostic characters above the rank of genus, which will be helpful for the easy identification of the grasses, even in their vegetative stages before flowering. The cluster analysis provides uses the statistical analysis program Minitab for each part on the basis of the diagnostic features. Due to the shortage of diagnostic morphological characteristics of grass leaves, culms, and caryopses, the study of complementary characters, like the anatomical features, has favored the clarification of taxonomic relationships between species and their correct identification. In this volume, readers will be able to easily identify the grass species based on the anatomical features described here. The volume will be of great interest both to grass specialists and as well as to generalists seeking state-of-the-art information on the diversity of grasses, the most ecologically and economically important of the families of flowering plants."--
Cover -- Half Title -- Title Page -- Copyright Page -- About the Authors -- Table of Contents -- Abbreviations -- Preface -- Introduction to the Book -- Introduction -- List of Grass Species Studied -- Materials and Methods -- Chapter 1: Leaf Anatomy -- Abstract -- 1.1. Introduction -- 1.2. Anatomical Features -- 1.3. Discussion and Identification Key -- 1.4. Cluster Analysis -- References -- Chapter 2: Culm Anatomy -- Abstract -- 2.1. Introduction -- 2.2. Anatomical Features -- 2.3. Discussion and Identification Key -- 2.4. Cluster Analysis -- References -- Chapter 3: Caryopsis Anatomy -- Abstract -- 3.1. Introduction -- 3.2. Anatomical Features -- 3.3. Discussion and Identification Key -- 3.4. Cluster Analysis -- References -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Grasses -- Identification; SCIENCE / General; SCIENCE / Life Sciences / Botany